Legal framework for preventing aesthetic procedures with modeling substances - Alicia María Tamayo Carbón; Reinol Delfín García Moreiro; Dagmara Cejas Bernet; Diana Katherine Cuastumal Figueroa (Centro Provincial de Información de Ciencias Médicas, 2023)
Currently, iatrogenic allogenosis is a condition recognized throughout the world, especially in Latin America, where the absence of control in the administration of unregulated substances for aesthetic purposes is evident, which has become an emerging problem due to the magnitude of complications, since some products, such as mineral oils, hydrocarbons, industrial silicone, generate serious consequences, both local and systemic, in the body. Many countries have not yet regulated the prohibition of this practice, although every day there are more campaigns to prevent it. However, at the same time the incidence of the disease increases worldwide due to the increase in these aesthetic procedures. In this regard, in Cuba, the growing number of people affected by this cause shows vulnerability in compliance with what has been established to date, that is why it is necessary to establish a legal framework of strict compliance that regulates the injection of modeling substances for aesthetic purposes.